2000
DOI: 10.1128/aac.44.8.2211-2213.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Activities of Ciprofloxacin, Clinafloxacin, Gatifloxacin, Gemifloxacin, Levofloxacin, Moxifloxacin, and Trovafloxacin against Epidemiologically Defined Acinetobacter baumannii Strains

Abstract: In vitro activities of seven fluoroquinolones against 140 clinical Acinetobacter baumannii isolates representing 138 different strain types were determined. The rank order of activity was clinafloxacin > gatifloxacin > levofloxacin > trovafloxacin > gemifloxacin ‫؍‬ moxifloxacin > ciprofloxacin. The 31 outbreak-related A. baumannii strains were significantly more resistant than were 109 sporadic strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 29 publications
1
5
1
2
Order By: Relevance
“…Resistance to antibiotics may provide certain A. baumannii strains with a selective advantage in an environment, such as the modern ICU, where microorganisms are confronted with extensive exposure to antimicrobials. Several researchers have observed that resistance rates in epidemic A. baumannii strains are significantly higher than those in sporadic A. baumannii strains (123,227,262,297). Resistance to the fluoroquinolones in particular was associated with epidemic behavior (227,262).…”
Section: Why Is a Baumannii A Persistent Hospital Pathogen?mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to antibiotics may provide certain A. baumannii strains with a selective advantage in an environment, such as the modern ICU, where microorganisms are confronted with extensive exposure to antimicrobials. Several researchers have observed that resistance rates in epidemic A. baumannii strains are significantly higher than those in sporadic A. baumannii strains (123,227,262,297). Resistance to the fluoroquinolones in particular was associated with epidemic behavior (227,262).…”
Section: Why Is a Baumannii A Persistent Hospital Pathogen?mentioning
confidence: 99%
“…Several researchers have observed that resistance rates in epidemic A. baumannii strains are significantly higher than those in sporadic A. baumannii strains (123,227,262,297). Resistance to the fluoroquinolones in particular was associated with epidemic behavior (227,262). Villers et al identified previous therapy with a fluoroquinolone as an independent risk factor for infection with epidemic A. baumannii, and it appeared that the selection pressure caused by the indiscriminate use of fluoroquinolones was responsible for the persistence and epidemic spread of multidrug-resistant A. baumannii clones for at least 5 years (586).…”
Section: Why Is a Baumannii A Persistent Hospital Pathogen?mentioning
confidence: 99%
“…Several researchers have observed that resistance rates in epidemic A. baumannii strains are significantly higher than those in sporadic A. baumannii strains (Dijkshoorn et al, 1996;Heinemann et al, 2000;Jawad et al, 1998;Koeleman et al, 2001).…”
Section: Resistance To Major Antimicrobial Drugsmentioning
confidence: 99%
“…baumannii bir çok antibiyotiğe dirençli olması ve salgınlar yapabilmesi nedeniyle hastane infeksiyon etkeni olarak özel bir yere sahiptir (15,16). Bu infeksiyonların tedavisinde karbapenemler, kinolonlar ve aminoglikozidler ilk seçenek olarak kullanılmaktadır.…”
unclassified
“…Yapılan çalışmalarda siprofloksasin, levofloksasin ve ofloksasin için %50'nin altında duyarlılık oranları ve yüksek MİK düzeyleri saptanmıştır (8,11). Heineman ve arkadaşlarının (15) çalışmasında yeni kinolonlardan klinafloksasin ve levofloksasinin in-vitro aktivitesinin siprofloksasine göre daha iyi olduğu belirlenmiştir. Çalışmamızda Acinetobacter suşlarının test edilen kinolonlara duyarlılık oranının %10'nun altında olduğu saptanmıştır.…”
unclassified